Kisspeptin and Polycystic Ovary Syndrome - Tang, Rong; Ding, Xiaohong; Zhu, Jianghu (Frontiers in Endocrinology, 2019)
Although the pathogenesis of Polycystic Ovary Syndrome (PCOS) is still unclear, the disturbance of hypothalamus-pituitary-gonad (HPG) axis is suspected to be the main culprit in the development of PCOS. Kisspeptin, a hypothalamic peptide encoded by KISS1 gene, is widely reported as a key factor in the regulation of luteinizing hormone (LH)/ follicular-stimulating hormone (FSH) secretion, which may be potentially involved with the development of PCOS. Objective: The objective of this study is to summarize the existing knowledge in the literature in terms of the circulating kisspeptin concentration in PCOS women, kisspeptin and metabolic profiles in PCOS women,kisspeptin expression in PCOS animal models. Method: A systematic literature search was conducted using “Pubmed”, “Embase”, “Web of Science” for all English language articles published up to July 2018 with the terms “PCOS”, “Stein-Leventhal Syndrome”, “Polycystic ovary syndrome”, “metastins” and “kisspeptin”. Conclusion: Overall, kisspeptin level is higher in PCOS population, which supports the hypothesis that over-activated KISS1 system lead to an enhanced HPG-axis activity, thereby cause irregular menstrual cycle and excessive androgen release in PCOS women.